Hybridoma cultivation in defined serum-free media: growth-supporting substances. I. Transferrin - Kovár, J; Franĕk, F (Folia biologica, 1985)
Effect of transferrin and effect of transferrin omission on growth of hybridomas in serum-free medium were studied. Transferrin at concentration 0.5 microgram/ml and higher concentrations stimulated growth of hybridoma cells. The optimum growth-supporting concentration of transferrin was 5 micrograms/ml. Omission of transferrin led to death of hybridoma T3-03 cells within 3-4 days. Omission of transferrin for a period of only 24 h damaged cells so severely, that they were unable to recover fully.
Keywords: Culture Techniques; Mice; kultivační média; Hybridomas; kultivační techniky; hybridomy; transferin; Animals; Cell Division; Transferrin; zvířata; myši; Culture Media; buněčné dělení